Preliminary evaluation of the use of bacteria isolated from the digestive tract of shrimp Litopenaeus vannamei as a source to accelerate the process of formation and development of bioflocs - Danyela Carla Elias Soares; Jade Oliveira Abreu; Jéssica Lucinda Saldanha da Silva; Oscarina Viana de Sousa (Acta Scientiarum. Animal Sciences, 2021)
This study aims at investigating to follow the formation and development of biofloc aggregates in a system with the introduction of an in vitro selected bacterial consortium (Bacillus thuringiensis, Bacillus sp., Staphylococcus cohnii) in order to induce fast formation of biofloc and to compare it to the development of spontaneous formation biofloc. Two experimental groups were evaluated for biofloc formation, SFT and IFT. The first refers to spontaneous (conventional) formation of the flocs and the second to induced formation (IFT), achieved through the consortium of potentially inducing bacteria. Both treatments presented a constant increase of bioflocs, however, in the IFT treatment, the microbial aggregates were larger and more uniform. By the end of the experiment, we verified that the aggregates formed in the IFT showed higher volume and lower sedimentation rate in comparison to the spontaneously formed ones. The results show that domestication in microbial communities is efficient as related to bioflocs, reducing instability during its formation and development.